2003
DOI: 10.1002/cncr.11479
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and toxicity of caspofungin in combination with liposomal amphotericin B as primary or salvage treatment of invasive aspergillosis in patients with hematologic malignancies

Abstract: Published models apply particle size to predict bioleaching reactor performance. In this study mathematical models predicting the overall reaction rate of a bioleach reactor system are developed to establish which particle parameters are necessary to describe reactor performance. Since the intrinsic leaching rate is surface area dependent, the inlet particle size and residence time are model inputs. Three models, distinguished by the incorporation of age and/or size distributions, were developed from first pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
194
2
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(206 citation statements)
references
References 37 publications
5
194
2
5
Order By: Relevance
“…Studies such as this may help reassure us that we are not doing any harm to patients but on the other hand, it is impossible to appreciate in these salvage studies which single or combination regimens are most successful. 37,38 The next step has been to study prospectively combination antifungal therapy for primary disease and this has been reported for an azole plus echinocandin, but there have been no blinded or randomized comparative trials and thus accurate insights into success of combination therapies are still uncertain. 39 In this study, the combination of voriconazole plus caspofungin as primary therapy for invasive aspergillosis in solid organ transplant recipients was compared to historical controls managed with a lipid formulation of amphotericin B. Ninety-day survival was 67.5% (27/40) among those who received combination antifungal therapy compared to 51% (24/47) of controls (HR 0.57, 95% CI 0.29-1.1).…”
Section: Challenge Recommendationmentioning
confidence: 99%
“…Studies such as this may help reassure us that we are not doing any harm to patients but on the other hand, it is impossible to appreciate in these salvage studies which single or combination regimens are most successful. 37,38 The next step has been to study prospectively combination antifungal therapy for primary disease and this has been reported for an azole plus echinocandin, but there have been no blinded or randomized comparative trials and thus accurate insights into success of combination therapies are still uncertain. 39 In this study, the combination of voriconazole plus caspofungin as primary therapy for invasive aspergillosis in solid organ transplant recipients was compared to historical controls managed with a lipid formulation of amphotericin B. Ninety-day survival was 67.5% (27/40) among those who received combination antifungal therapy compared to 51% (24/47) of controls (HR 0.57, 95% CI 0.29-1.1).…”
Section: Challenge Recommendationmentioning
confidence: 99%
“…50 Response rates from retrospective reports in heterogeneous patient populations have been inconsistent. 45,53,54 Favorable responses were observed among HSCT patients failing polyene-based therapy for invasive aspergillosis with a combination of voriconazole and caspofungin compared to voriconazole monotherapy. 55 Only one recent randomized-controlled trial in IC suggested that a combination of fluconazole and amphotericin B deoxycholate may have advantages over fluconazole monotherapy.…”
Section: Salvage Monotherapymentioning
confidence: 99%
“…Los resultados de la aplicación de las combinaciones de voriconazol o anfotericina B liposomal con caspofungina [23][24][25] (BII) no son excesivamente alentadores, ya que el éxito terapéutico es parecido al hallado en controles históricos de pacientes con aspergilosis pulmonar invasiva tratados con cada fármaco por separado. En cualquier caso, el número global de pacientes es muy pequeño y sería recomendable la realización de un ensayo clínico controlado con un número más elevado.…”
Section: Tratamiento Antifúngicounclassified